Evaluation of Empiric Vancomycin for Fevers During High-dose Cytarabine Administration. Issue 7 (October 2021) - Hoover, Alex; Zimmerman, Jessica A.O.; Wiese, Sawyer; Modi, Arunkumar
Abstract : Background: Cytarabine is a nucleoside analog used in chemotherapy regimens for the treatment of multiple hematologic malignancies. One of the known adverse effects of cytarabine, particularly in patients receiving high-dose cytarabine (HDAC), is drug-induced fever. Multiple studies have demonstrated an increased risk of viridans group streptococcal bacteremia in patients who have received HDAC. For this reason, our institution and several other institutions across the country routinely include vancomycin as empiric coverage for patients who develop fever during HDAC, due to concern for resistance to cephalosporin monotherapy. Materials and Methods: Patient demographic, diagnosis, treatment, and outcome information was collected by electronic chart review for each HDAC infusion from 2007 to August 2018 at the University of Iowa Stead Family Children's Hospital. If fever was documented during or within 24 hours of HDAC, additional information was collected regarding patient outcome and diagnostic testing. Results: Of 208 HDAC administrations documented, patients developed fevers during the course on 82 occasions (39.4%). A median of 3 blood cultures per febrile period were obtained from time of fever onset during HDAC administration through >24 hours afebrile. One blood culture was positive for an oral flora organism determined by the microbiology lab report to be a likely contaminant. There were no other positive blood cultures in non-neutropenic or neutropenic patients. Conclusion: Fever due to HDAC is relatively common but appears to frequently lack association with bacteremia during the time of HDAC administration. Broad-spectrum empiric antibiotic regimens including vancomycin may be unnecessary for these patients, particularly before they become neutropenic. Abstract : Supplemental Digital Content is available in the text.